2018
DOI: 10.1186/s40104-018-0305-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of methanogenesis, ruminal fermentation and fiber digestibility in ruminants following elimination of protozoa: a meta-analysis

Abstract: BackgroundRuminal microbes are vital to the conversion of lignocellulose-rich plant materials into nutrients for ruminants. Although protozoa play a key role in linking ruminal microbial networks, the contribution of protozoa to rumen fermentation remains controversial; therefore, this meta-analysis was conducted to quantitatively summarize the temporal dynamics of methanogenesis, ruminal volatile fatty acid (VFA) profiles and dietary fiber digestibility in ruminants following the elimination of protozoa (also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 57 publications
2
16
1
2
Order By: Relevance
“…These observations are consistent with the evidence that ciliates survive by digesting rumen bacteria, thus playing an important role in the inefficient use of dietary protein by ruminants and that protozoa are indirectly involved in methane production, as they harbour an active population of methanogenic archaea both on their external and internal surfaces (Morgavi et al, 2010). A recent meta-analysis exploring time-dependent effects of removing protozoa (Li et al, 2018) concluded that subsequent increases in methanogens, fungi and cellulolytic bacteria counteracted defaunation-induced effects on rumen fermentation, suggesting that defaunation might not always lead to lower levels of methane production. Protozoa also seem to stabilize rumen fermentation increasing rumen pH (Williams and Coleman, 1992), possibly because protozoa consume lactate more rapidly than bacteria (Newbold et al, 1986).…”
Section: Protozoasupporting
confidence: 83%
“…These observations are consistent with the evidence that ciliates survive by digesting rumen bacteria, thus playing an important role in the inefficient use of dietary protein by ruminants and that protozoa are indirectly involved in methane production, as they harbour an active population of methanogenic archaea both on their external and internal surfaces (Morgavi et al, 2010). A recent meta-analysis exploring time-dependent effects of removing protozoa (Li et al, 2018) concluded that subsequent increases in methanogens, fungi and cellulolytic bacteria counteracted defaunation-induced effects on rumen fermentation, suggesting that defaunation might not always lead to lower levels of methane production. Protozoa also seem to stabilize rumen fermentation increasing rumen pH (Williams and Coleman, 1992), possibly because protozoa consume lactate more rapidly than bacteria (Newbold et al, 1986).…”
Section: Protozoasupporting
confidence: 83%
“…Morgavi, Marin, Jouany, and Ranilla (2012) and Li et al. (2018) associated the reduction of protozoa to a lower production of acetate and butyrate, but this condition was not confirmed in our in vitro tests (Table 2). Furthermore, tannins are known to form complexes with feed protein or inhibit the protease and urease enzymes in the rumen (Patra & Aschenbach, 2018; Patra & Saxena, 2010) thus lowering the rumen ammonia concentrations.…”
Section: Resultscontrasting
confidence: 56%
“…However, such compensation requires enough time of adaptation and the recent meta‐analysis of Li et al. (2018) suggested that after 12 weeks of defaunation, the reductions in methane are no longer evident. Moreover, Colombini et al.…”
Section: Resultsmentioning
confidence: 99%
“…Opposite trends of acetate and propionate molar proportion resulted in decreased A:P ratio in most of the inhibitor treatments, which is consistent with decreased A:P ratio observed in defaunated sheep fed high-concentrate diet (Mendoza et al, 1993). A similar VFA profile shift was also reported in a recent meta-analysis of the defaunation effect on rumen fermentation (Li et al, 2018). The bacterial population shifts in the inhibitor treatments could also contribute to the shifted VFA profile.…”
Section: Discussionsupporting
confidence: 85%